Pengaruh Kompetensi Profesional dan Efektivitas Kerja Terhadap Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka - Randy Algian Tezar Mulyadi; Sri Suwarsi (UNISBA Press, 2022)
Abstract. This study aims to determine 1) Professional Competence of teachers at SMP IT At-Tadzkir Majalengka Regency. 2) The level of work effectiveness of teachers at SMP IT At-Tadzkir Majalengka Regency. 3) Teacher Performance at SMP IT At-Tadzkir Majalengka Regency. 4) The Effect of Professional Competence on Teacher Performance at SMP IT At-Tadzkir Majalengka Regency. 5) The Effect of Work Effectiveness on Teacher Performance at SMP IT At-Tadzkir Majalengka Regency. 6) Effect of Professional Competence and Work Effectiveness on Teacher Performance at SMP IT At-Tadzkir Majalengka Regency. The type of research used is quantitative with descriptive and verification analysis methods. In operating the calculations using the SPSS 25.0 program. The variables in this study are Professional Competence, Work Effectiveness and Teacher Performance. Collecting data obtained through questionnaires, documentation, and literature study. The sampling technique is saturated sampling. Respondents of this study were teachers at SMP IT At-Tadzkir Majalengka Regency, amounting to 30 people.The results of this study conclude that: 1) Professional competence of teachers at SMP IT At-Tadzkir Majalengka Regency is in the high category. 2) The work effectiveness of teachers at SMP IT At-Tadzkir Majalengka Regency is in the high category. 3) Teacher performance at SMP IT At-Tadzkir Majalengka Regency is in the high category. 4) Professional competence partially has a significant effect on teacher performance at SMP IT At-Tadzkir, Majalengka Regency. 5) Work effectiveness partially has a significant effect on teacher performance at SMP IT At-Tadzkir, Majalengka Regency. 6) Professional Competence and Work Effectiveness simultaneously have a significant effect on Teacher Performance at SMP IT At-Tadzkir, Majalengka Regency. It can be said that there is an influence between Professional Competence and Work Effectiveness on Teacher Performance at SMP IT At-Tadzkir Majalengka Regency. Abstrak. Penelitian ini bertujuan untuk mengetahui 1) Kompetensi Profesional guru di SMP IT At-Tadzkir Kabupaten Majalengka. 2) Tingkat Efektivitas Kerja guru di SMP IT At-Tadzkir Kabupaten Majalengka. 3) Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka. 4) Pengaruh Kompetensi Profesional terhadap Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka. 5) Pengaruh Efektivitas Kerja terhadap Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka. 6) Pengaruh Kompetensi Profesional dan Efektivitas Kerja terhadap Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka. Jenis penelitian yang digunakan adalah kuantitatif dengan metode analisis deskriptif dan verifikatif. Dalam mengoperasikan perhitungannya menggunakan program SPSS 25.0. Variabel dalam penelitian ini Kompetensi Profesional, Efektivitas Kerja dan Kinerja Guru. Pengumpulan data yang diperoleh melalui kuesioner, dokumentasi, dan studi pustaka. Teknik penarikan sampel adalah sampling jenuh. Responden penelitian ini adalah guru di SMP IT At-Tadzkir Kabupaten Majalengka yang berjumlah 30 orang. Hasil penelitian ini menyimpulkan bahwa: 1) Kompetensi Profesional guru di SMP IT At-Tadzkir Kabupaten Majalengka termasuk kategori tinggi. 2) Efektivitas Kerja guru di SMP IT At-Tadzkir Kabupaten Majalengka termasuk kategori tinggi. 3) Kinerja guru di SMP IT At-Tadzkir Kabupaten Majalengka termasuk kategori tinggi. 4) Kompetensi Profesional secara parsial berpengaruh signifikan terhadap Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka. 5) Efektivitas Kerja secara parsial berpengaruh signifikan terhadap Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka. 6) Kompetensi Profesional dan Efektivitas Kerja secara simultan berpengaruh signifikan terhadap Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka. Dapat disimpulkan bahwa terdapat pengaruh antara Kompetensi Profesional dan Efektivitas Kerja terhadap Kinerja Guru di SMP IT At-Tadzkir Kabupaten Majalengka.